2018
DOI: 10.17344/acsi.2017.3613
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic, Structural and Density Functional Theory (DFT) Studies of Two Oxazol-5-one Derivatives

Abstract: In this study, two oxazol-5-one derivatives, C 20 H 20 N 2 O 2 (1) and C 21 H 22 N 2 O 2 (2), were synthesized by getting condensed p-N,N-diethylaminobenzaldehyde with two presented hippuric acid derivatives and in further studies they were analysed spectrochemically. Molecular and crystal structures of the compounds were determined by single-crystal X-ray diffraction and the results revealed that the molecular packing of the crystal structures were stabilized by weak intraand intermolecular interactions also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It can also be readily prepared from N-protected amino acids by dehydration. It also possesses several biological activities like immune modulatory, 10 pesticidal, 11 antidiabetic activity, 12 antitubercular 13 anti-cancer, 14 anti-HIV, 15 anticonvulsant, 16 anti-angiogenic, 17 analgesic and anti-inflammatory activity. 18 Recently research has explored all these biological activities and believed that most of the reported diseases would be occurring only because of a demand for antioxidants in the human system.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be readily prepared from N-protected amino acids by dehydration. It also possesses several biological activities like immune modulatory, 10 pesticidal, 11 antidiabetic activity, 12 antitubercular 13 anti-cancer, 14 anti-HIV, 15 anticonvulsant, 16 anti-angiogenic, 17 analgesic and anti-inflammatory activity. 18 Recently research has explored all these biological activities and believed that most of the reported diseases would be occurring only because of a demand for antioxidants in the human system.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain highly accurate geometries and physical properties for molecules that are built from electronegative elements, expensive Ab initio/MP2 electron correlation methods are required. 8 Density functional theory methods [9][10][11][12][13][14] offer an alternative use of inexpensive computational methods which could handle relatively large molecules. [15][16][17][18][19][20] Quantitative structure-activity relationships (QSAR) [21][22][23][24][25] are attempts to correlate molecular structure, or properties derived from molecular structure, with a particular kind of chemical or biochemical activity.…”
Section: Introductionmentioning
confidence: 99%